Efficiency Of Swale And Dry Pond For Stormwater Management - Manap, Asnol Adzhan Abd. (2009)
The implementation of the Best Management Practices (BMPs) in a drainage system through the Stormwater Management Manual For Malaysia or better known as Manual Saliran Mesra Alam (MSMA), focusing on constructed swale and dry pond, was studied. The study was carried out on the Bio-Ecological Drainage System (BIOECODS) at Engineering Campus, Universiti Sains Malaysia (USM), Nibong Tebal, Pulau Pinang, located in Kerian River Basin. Besides the implication of the swale and dry pond toward the inflow hydrograph of a series of ponds (detention pond, wetland and recreational pond known as ECOPOND) in managing stormwater quantity in development area, factors that affect the effectiveness of the swale and dry pond using hydrologic and hydraulic model were also identified.